Analysis Of Capital Structure, Profitability, Liquidity, Com-pany Growth, And Firm Value - Rindy Maylita Hapsari; Sjarief Hidajat (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to examine the effect of capital structure, profitability, liquidity, and company growth on firm value in the construction service sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The background of this research is based on the fluctuations in firm value within the construction service industry over the past five years, which have the potential to reduce investor interest and influence market perception. The research employs a quantitative approach using purposive sampling, resulting in a sample of 7 companies out of a total population of 18. The data used are secondary data in the form of annual reports, analyzed using the Partial Least Squares (PLS) method with the assistance of Smart-PLS version 4.0 software. The findings indicate that capital structure and liquidity have a positive and significant effect on firm value, while profitability and company growth do not show a significant effect.